Bioaugmentation by Pediococcus acidilactici AAF1-5 Improves the Bacterial Activity and Diversity of Cereal Vinegar Under Solid-State Fermentation - Zhang, Qiang; Zhao, Cuimei; Wang, Xiaobin; Li, Xiaowei; Zheng, Yu; Song, Jia; Xia, Menglei; Zhang, Rongzhan; Wang, Min (Frontiers in Microbiology, 2021)
Bioaugmentation technology may be an effective strategy to improve the solid-state fermentation rate and utilization of raw materials for traditional vinegar production. The relationship between bacteria and fermentation process was analyzed to rationally design and perform bioaugmented solid-state fermentation of Tianjin Duliu mature vinegar (TDMV). Fermentation process was highly correlated with Acetobacter, Lactobacillus, and Pediococcus contents, which were the core functional microorganisms in TDMV fermentation. Pediococcus acidilactici AAF1-5 was selected from 20 strains to fortify the fermentation due to its acidity and thermal tolerance. Bioaugmentation was performed in the upper layer of TDMV fermentation. P. acidilactici AAF1-5 colonized and then spread into the lower layer to improve the fermentation. Result showed that the fermentation period was 5 days less than that of the control. Meanwhile, the non-volatile acid, lactic acid, amino nitrogen, and reducing sugar contents in the bioaugmented TDMV increased by 53%, 14%, 32%, and 36%, respectively, compared with those in the control. Bioaugmentation with P. acidilactici AAF1-5 not only improved the utilization of starch from 79% to 83% but also increased the bacterial community diversity.